Letramento racial crítico: o encantamento do livro “o mundo no black power de Tayó” em uma proposição didática - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
The present research aims to analyze the Critical Racial Literacy (LRC) within the children's literature so as to work on racial identities. This work aims to research how the book “The world in Tayó’s Black Power” addresses the identity of black children and how the activities of a PD with an emphasis on LRC can collaborate to strengthen the racial identity of black children. To that end, I tried to answer some research questions: 1) How does the book “O Mundo no Black Power de Tayó” address the identity of black children? 2) How to work on PD activities with an emphasis on LRC? Theoretically, the study was supported by authors such as Gomes (2005), Muniz (2010), Melo (2015), Ferreira (2014, 2016, 2017), among others, who dedicate their studies to racial issues. For reflections on literacy (s), researchers such as Soares (2004), Kleiman (2014) and Street (2018) were used. On the perspective of teaching from the LRC, the basis was Ladson-Billings (2001) and Ferreira (2014), who address the Critical Racial Theory (CRT) in education. About children's literature, I was guided by the researches carried out by Coelho (2000), Debus (2017), Hunt (2010), Rosemberg (1985) and Zilberman (1987), among others. The methodology used in this research is qualitative and Applied Linguistics: analysis of children's literature and SD books and, finally, the generation of themes for systematizing the data. The results indicate that LRC is an important ally of teachers in the classroom, when it comes to working with the racial identities of black children. In this perspective, it was possible to reach conclusions that demonstrate that the work of teachers from a children's literature book, with protagonist black characters, can positively address the identity of black children. In addition, it was also possible to understand that a PD with an emphasis in LRC, can collaborate to strengthen the racial identity of black children.
Keywords: Literatura Infantil; Identidade Racial; Letramento Racial Crítico; Children's Literature; Racial identity; Critical Racial Literacy; CNPQ::LINGUISTICA, LETRAS E ARTES